1997
DOI: 10.1109/22.643847
|View full text |Cite
|
Sign up to set email alerts
|

Wide-band SSB subharmonically pumped mixer MMIC

Abstract: To achieve low conversion-loss and high imagerejection performance in the wide band for up and down conversion, an SSB subharmonically pumped mixer using an inphase RF divider/combiner is proposed. The SSB mixer monolithic microwave integrated circuit (MMIC) is integrated in a small area of 1.8 2 1.3 mm 2 and shows good performance at 21.6 to 30.8 GHz.Index Terms-Image-rejection mixer, monolithic microwave integrated circuit (MMIC), quasi-lumped stub, subharmonically pumped mixer, wide-band mixer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The antiparallel pair diode is chosen as the mixing core and each diode is two-finger 30-tm. The quasi-lumped matching topology is used to reduce the size of quarter-wavelength open/short stubs for miniature circuit implementations [8], as shown in Fig. 2.…”
Section: A Sub-harmonic Mixermentioning
confidence: 99%
“…The antiparallel pair diode is chosen as the mixing core and each diode is two-finger 30-tm. The quasi-lumped matching topology is used to reduce the size of quarter-wavelength open/short stubs for miniature circuit implementations [8], as shown in Fig. 2.…”
Section: A Sub-harmonic Mixermentioning
confidence: 99%
“…Unfortunately, the "open" frequency of the shortened stub is not a harmonic of the "short" frequency; thus, it is not suitable for doublers. To overcome this problem, a quasi-lumped method with asymmetric shunt capacitors has been proposed [15]. The with a lumped inductor, as shown in Fig.…”
Section: Quadrupler Mmic Designmentioning
confidence: 99%
“…Based on the above features, the authors have proposed new circuit topologies of even harmonic mixers and their applications: even harmonic up-converters with extremely low virtual LO leakage [7], [8], even harmonic modulators with extremely low carrier leakage [9], and even harmonic direct-conversion receivers with low second-order distortion [10]. Since the publication of the authors' initial works, several studies on even harmonic mixers have been reported [11]- [15]. Even harmonic mixers have issues related to their lower output power and higher conversion-loss dependence on the LO power.…”
Section: Introductionmentioning
confidence: 97%